Pengaruh Model Pembelajaran Problem Based Instruction (PBI) Terhadap Hasil Belajar IPS Pada Peserta Didik Kelas V SDN 6 Kendari - Mahdalena Mahdalena; La Sisi; Ahmad Ahmad (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
The purpose of this study was to determine the effect of the Problem Based Instruction (PBI) model on social studies learning outcomes in class V students of SD Negeri 6 kendari. This research is expected to make the development of science about the effect of the Problem Based Instruction (PBI) model on social studies learning outcomes, For students, this research can be useful to help improve student activeness and student learning outcomes in social studies learning. This research uses a quantitative approach. This type of research is a type of experimental research because of the provision of learning treatment using a learning model that is Problem Based Instruction (PBI) model. Experimental research aims to describe things that happen if the class under study when given treatment.The target of our experimental class trial is class VA, VB SD Negeri 6 kendari with a total of 29 students. in this study. the average value of students' social studies learning outcomes before learning (pretest) is 47.41 and the average value of students' social studies learning outcomes after learning (posttest) is 74.14. With the difference or difference in the average pretest and posttest scores of 26.73 this indicates an increase in student social studies learning outcomes by using the Problem Based Instruction (PBI) model. then the conclusion in this study is Based on the results of hypothesis testing conducted using the One-Sample Test obtained sig. value of 0.000. This means that the value of sig. 0.05 so it can be concluded that H0 is rejected and H1 is accepted, meaning that there is an effect of Problem Based Instruction (PBI) model on social studies learning outcomes of fifth grade students of SD Negeri 6 Kendari.